2014
DOI: 10.1007/s00428-014-1588-4
|View full text |Cite
|
Sign up to set email alerts
|

The PI3K/AKT/mTOR pathway is activated in gastric cancer with potential prognostic and predictive significance

Abstract: Signaling pathway alterations are important in the development of gastric cancer (GC). Deregulation of the PI3K/AKT/mTOR pathway plays a crucial role in the regulation of multiple cellular functions including cell growth, proliferation, metabolism, and angiogenesis. Our goal was to assess expression of proteins involved in the PI3K/AKT/mTOR pathway by immunohistochemistry (IHC) in tumor and nontumor gastric mucosa from patients with advanced GC. We evaluated 71 tumor and 71 nontumor gastric mucosa samples from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
139
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(152 citation statements)
references
References 48 publications
5
139
0
1
Order By: Relevance
“…8 Activation of PI3K is also known to enhance the mucin secretion (Muc4), 9 and transcriptional upregulation of Muc4 is recognized to have antiapopitotic and mitogenic effects in various tumors. 10,11 PIK3 activation and Muc4 overexpression have also been found in gastric adenocarcinomas, 12,13 which further supports the role of ErbB2/ErbB3 – PI3K cascade activation in the formation of mucin-laden neoplastic SRCs.…”
Section: Discussionsupporting
confidence: 57%
“…8 Activation of PI3K is also known to enhance the mucin secretion (Muc4), 9 and transcriptional upregulation of Muc4 is recognized to have antiapopitotic and mitogenic effects in various tumors. 10,11 PIK3 activation and Muc4 overexpression have also been found in gastric adenocarcinomas, 12,13 which further supports the role of ErbB2/ErbB3 – PI3K cascade activation in the formation of mucin-laden neoplastic SRCs.…”
Section: Discussionsupporting
confidence: 57%
“…Since the PI3K/AKT/mTOR pathway has previously been reported to be up-regulated in gastric cancer (GC) [7, 8], we focused our study on miR-101-2, miR-125b-2 and miR-451a, which are according to TargetScan, PicTar and miRanda related to MTOR, PIK3CB and TSC1 expression, respectively. miR-101-2 is encoded by a gene located in 9p21, a chromosomal region exhibiting a high frequency of allelic loss in several cancers including liver, colon, pancreas and breast cancer, and in neuroblastoma [2326].…”
Section: Discussionmentioning
confidence: 99%
“…The p21(now known as CDKN1A) has important roles in the proliferation of various cancer types, including glioma [18]. In addition, Wong et al reported that KDM5B promotes cell cycle progression via direct p21 repression [16].…”
Section: Kdm5b Promoted Glioma Cells Proliferation Via Downregulatingmentioning
confidence: 97%